Improving Digital Skills of Islamic Boarding School-Based MSMEs through Project-Based Vocational Training - Setiawan, Heri Cahyo Bagus; Ilham, Ilham; Latukismo, Tatag Herbayu; Fatimah, Nuzulul (Universitas Muhammadiyah Gresik, 2025)
Islamic boarding schools in Indonesia have long been known as centers of religious education, but in this digital era, Islamic boarding schools are faced with the challenge of transforming into community empowerment institutions through vocational and entrepreneurial education. This study examines the effectiveness of project-based vocational training in improving the digital skills of MSME actors fostered by the Mukmin Mandiri Islamic Boarding School in Sidoarjo. This training includes creating marketplace accounts, managing social media, and creating digital product catalogs. Through a project-based learning approach, participants are given the opportunity to learn directly through real experiences. The study used a quantitative method with pre-test and post-test experiments on 45 participants who participated in the training. The results showed a significant increase in digital skills, with an average score increasing from 40.00 (pre-test) to 85.00 (post-test), reflecting the effectiveness of this training in improving the digital capabilities of MSME actors. These findings confirm that the project-based training model not only improves technical skills, but also strengthens self-confidence, adaptive mindsets, and digital entrepreneurial motivation, while strengthening the role of Islamic boarding schools in encouraging community-based economic empowerment in the digital era.